On What There Is Not : Extensible markup language and rules for making inferences - Tambassi, Timothy (Logic and Logical Philosophy, 2025)
This paper investigates how the use of different rules for making inferences affects our understanding of what certain Extensible Markup Language (XML) documents do not represent. The aim is to show that we can infer different, contrasting things from the same XML documents, thereby weakening the communication that XML is supposed to support. There are three main reasons why the paper focuses on XML. First, XML, as a metalanguage, has no inherent rules for making inferences, but it also has no constraints on the technologies, systems, or theories that support or define the rules that can be used in conjunction with it. Second, XML is still widely used, and there are many other markup languages based on XML. This means that the critical analysis of these pages is, in principle, extendable to contexts where XML is involved and/or the rules for making inferences are not inherently supported. Third, since XML is explicitly intended to support communication between people, between software applications, and between people and software applications, this analysis may also shed new light on some of the theoretical assumptions behind such communication.